Kesiapan dalam Implementasi Kurikulum Merdeka Belajar - Rahmi Ali; La Ode Amaluddin; La Ode Nursalam; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Curriculum and teachers cannot be separated from each other because teachers have a big role in the success or failure of implementing the curriculum. The aim of this research is to determine teacher readiness in implementing the merdeka curriculum as well as the supporting and inhibiting factors faced by schools in implementing the merdeka belajar curriculum. This type of research is descriptive with mixed methods, combining qualitative and quantitative. Data collection techniques used questionnaires and interviews. The subjects in this research were all class X teachers who implemented the merdeka belajar curriculum, totaling 31 teachers. The data analysis technique uses descriptives in the form of percentages The results of the study show that the readiness of Senior High School 1 Pasarwajo teachers in implementing the merdeka belajar curriculum is in the